The estimation of the efficiency of the technologies of geological prospecting and geotechnological wells drilling - V. V. Kulikov; M. S. Frolova (Известия высших учебных заведений: Геология и разведка, 2016)
An efficiency criterion of boring technologies efficiency estimation is considered, simultaneously taking into account a 1 m drilling cost or a 1 day well installation cost and a day labor productivity. The foundation of the criterion is given and a general formula for this criterion is suggested. The example of the calculation with the use of the formula is presented.